Liczebność ludności polskojęzycznej na Powiślu przed pierwszą wojną światową na podstawie pruskich spisów językowych = The size of the polish-speaking population in Vistulaland before the First World War based on the Prussian language statistics - Belzyt, Leszek (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Powiśle is an area lying on the right bank of the lower Vistula. In the period before the First World War it was considered to be the Prussian districts Elblag, Malbork, Kwidzyn, Sztum and Susz. The number of Polish people, who lived there before the First World War can be determined on the basis of the data of the Prussian language statistics, mainly from the years 1890-1910 and the results registers of primary school pupils from 1886-1911.
Keywords: pruska statystyka językowa; Powiśle; mniejszość polska - Niemcy; Prussian language statistic; Vistulaland; polish minority in Germany